COVID-19 pneumonija: kada negativni PCR ne isključuje oboljenje - Stajic, Mladen; Maksimović, Žana; Verhaz, Antonija (Scripta Medica, 2020)
In diagnosing COVID-19, false negative findings from the biological sample taken from a mucosal swab of the upper respiratory tract and tested with the real-time reverse-transcription polymerase chain reaction (RT-PCR) technique have been reported. This patient has had a proven contact with an infected person, clear symptoms of viral respiratory disease, yet negative test results on the fifth day of self-isolation. On repeated test after 48 hours, on the 7th day of isolation, due to persistence of some symptoms, he tested positive for SARS-CoV-2. The existence of symptoms and characteristic sings after laboratory and radiological analysis of the patient prompted the repetition of the tests, which at the end led to the confirmed diagnosis and the possibility for adequate treatment of the patient as well.